2020
DOI: 10.1093/geront/gnz195
|View full text |Cite
|
Sign up to set email alerts
|

Berlin Inventory of Caregiver Stress—Dementia (BICS-D)

Abstract: Background and Objectives Dementia is becoming increasingly prevalent and family caregivers have been providing most of the care for persons with dementia. This caregiving is a mentally and physically demanding task. “The Berlin Inventory of Caregiver Stress—Dementia” (BICS-D) is a theory driven, multidimensional assessment which was developed as part of the Longitudinal Dementia Caregiver Stress Study (LEANDER). Research Design and Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Medical professionals must be aware of the burdens associated with medication management, and comprehensive drug training should be available for all caregivers (Aston et al., 2017). Respite care and professional caregiving arrangements have proven to decrease these tasks for caregivers, reducing costs for health systems due to preventive care, and well‐developed, tailored support plans that proffer in‐home aid are flexible and adaptable (Schlomann et al., 2021). Insurance coverage for PLWD could expand to include occupational therapists and recreational activities to assist informal caregivers with daily tasks (Amato et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Medical professionals must be aware of the burdens associated with medication management, and comprehensive drug training should be available for all caregivers (Aston et al., 2017). Respite care and professional caregiving arrangements have proven to decrease these tasks for caregivers, reducing costs for health systems due to preventive care, and well‐developed, tailored support plans that proffer in‐home aid are flexible and adaptable (Schlomann et al., 2021). Insurance coverage for PLWD could expand to include occupational therapists and recreational activities to assist informal caregivers with daily tasks (Amato et al., 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Our all‐female sample reported that the delivery of a broad spectrum of tasks appeared to restrict their social participation. As such, thoughtful interventions are needed to prevent isolation and accommodate those caregivers typically not considered at ‘high risk’, particularly older spouses who reported higher levels of burden (Riffin et al., 2017; Schlomann et al., 2021). Psychosocial brief programming is known to prepare caregivers with education on perplexing dementia care needs and has been shown to increase levels of self‐efficacy and decrease depressive symptoms compared to passive learning methods (Meyer et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The result of the factor analysis turned out to be identical to those performed 40 years ago in Britain [ 20 ], 15 years ago in Norway [ 23 ], and recently in Germany [ 38 ] and Thailand [ 32 ], which displays the usefulness of the scale over time and across cultures. Being a next-of-kin carer of someone suffering from dementia of any aetiology is stressful [ 15 , 16 , 17 , 18 , 19 , 39 , 40 , 41 , 42 , 43 , 44 ]. The results of this study are well-aligned with the existing research that suggests some carers experience a great deal of burden; this is also the case for Slovak next-of-kin carers for dementia sufferers.…”
Section: Discussionmentioning
confidence: 99%
“…The underlying variables of the primary DemNet-D study are presented in Additional file 1: Appendix A. The selected variables originate from sociodemographic questions, the Instrument for Assessing Home-Based Care Arrangements for Persons with Dementia (D-IVA) [12], the Berlin Inventory of Caregiver Stress-Dementia (BICS-D) [20], the Functional Assessment Staging (FAST) tool [21] and the Quality of Life in Alzheimer's Disease (QOL-AD proxy) questionnaire [22].…”
Section: Measurementsmentioning
confidence: 99%